Comfortable Mrs. Crook, and other sketches - Lamb, Ruth, 1829-1916 (Salt Lake City, UT : Project Gutenberg, 2024)
"Comfortable Mrs. Crook, and Other Sketches" by Ruth Lamb is a collection of character sketches written during the late 19th century. The narrative centers around Mrs. Jemima Crook, a seemingly self-sufficient widow whose life and interactions with her neighbors reveal layers of solitude, self-centeredness, and a lack of compassion for others. Throughout the sketches, the author likely explores themes of kindness, isolation, and the human experience in a rapidly changing world. The opening of the work introduces Mrs. Crook as a woman proud of her comfortable position following her husband$1 (Bs death. She is portrayed as a person who prefers solitude and self-reliance, frequently repelling attempts by neighbors to engage her in acts of kindness or community involvement. Notably, Mrs. Crook is indifferent to the plight of those less fortunate, as exemplified by her harsh treatment of local children drawn to her flower garden. As the narrative progresses, hints of her inner turmoil regarding her life choices begin to surface, particularly when she is contrasted with her compassionate servant, Fanny, and the ailing Miss Lawton, offering the promise of deeper character development in subsequent chapters. (This is an automatically generated summary.)s
Comfortable Mrs. Crook -- Can't afford to play -- Walking too big -- Winkles.
Release date is 2024-05-08
Keywords: Christian life -- Fiction; Conduct of life -- Fiction; English fiction -- 19th century; Short stories, English